Embodied Learning and Trauma in the Classroom and in Practice - Ann L. Swartz (Adult Education Research Conference, 2010)
This study sought to understand how RN-BS clinical students learn through their bodies and how these patterns relate to trauma. Use of an experiential, embodied pedagogy led to emergence of embodied connection with self and new patterns of self-care, professional knowledge and action.